Malnutrition-related mortality trends in older adults in the United States from 1999 to 2020 - Naydeen Mostafa; Ahmed Sayed; Omar Rashad; Omar Baqal (BMC Medicine, 2023)
Abstract Background Malnutrition mortality in older adults is underrepresented in scientific literature. This obscures any recent changes and hinders needed social change. This study aims to assess malnutrition mortality trends in older adults (≥ 65 years old) from 1999 to 2020 in the United States (U.S.). Methods Mortality data from the Centers for Disease Control and Prevention’s (CDC) Wide-Ranging Online Data for Epidemiology Research (WONDER) database were extracted. The ICD-10 Codes E40 – E46 were used to identify malnutrition deaths. Crude mortality rates (CMR) and age-adjusted mortality rates (AAMR) were extracted by gender, age, race, census region, and urban–rural classification. Joinpoint regression analysis was used to calculate annual percentage changes (APC) of AAMR by the permutation test and the parametric method was used to calculate 95% confidence intervals. Average Annual Percentage Changes (AAPC) were calculated as the weighted average of APCs. Results Between 1999 and 2020, 93,244 older adults died from malnutrition. Malnutrition AAMR increased from 10.7 per 100,000 in 1999 to 25.0 per 100,000 in 2020. The mortality trend declined from 1999 to 2006 (APC = –8.8; 95% CI: –10.0, –7.5), plateaued till 2013, then began to rise from 2013 to 2020 with an APC of 22.4 (95% CI: 21.3, 23.5) and an overall AAPC of 3.9 (95% CI: 3.1, 4.7). Persons ≥ 85 years of age, females, Non-Hispanic Whites, residents of the West region of the U.S., and urban areas had the highest AAPCs in their respective groups. Conclusion Despite some initial decrements in malnutrition mortality among older adults in the U.S., the uptrend from 2013 to 2020 nullified all established progress. The end result is that malnutrition mortality rates represent a historical high. The burden of the mortality uptrends disproportionately affected certain demographics, namely persons ≥ 85 years of age, females, Non-Hispanic Whites, those living in the West region of the U.S., and urban areas. Effective interventions are strongly needed. Such interventions should aim to ensure food security and early detection and remedy of malnutrition among older adults through stronger government-funded programs and social support systems, increased funding for nursing homes, and more cohesive patient-centered medical care.